Evaluation of Fungicides and Fungicidal Spray Schedule for the Management of Angular Leaf Spot of Common Bean - Mekonen, Shiferaw (Canadian Journal of Agriculture and Crops, 2017)
Angular Leaf Spot (ALS), caused by Phaeoisariopsisgriseola (Sacc.), is one of the major diseases of common bean in the Southern Ethiopia.The objective of the experiment was to select fungicides and spray intervals to recommend low cost management options for the control of ALS disease. The experiment was carried out under natural epidemic at Awassa Agricultural Research Center in Southern Ethiopia during 2013 -2014. The study consisted of five different fungicides (Ridomil Gold, Penncozeb, Curzate, Tilt 250 EC and Bumper 25 EC) in combination with two spray intervals ( 7 and 14 days) using two common bean varieties (HawassaDume and Red Wolaita) having dissimilar levels of reaction to ALS. The treatments were laid using Randomized Complete Block Design (RCBD) in factorial arrangement. All fungicides tested were found to be effective in controlling the ALS disease as compared to unsprayed treatment. Ridomil Gold was the most effective fungicide in reducing the disease severity and yield loss,followed by Curzate and Penncozeb, where asPropiconazole fungicides (Tilt 250 and Bumper) showed high AUDPC value as compared to the other fungicides. Ridomil Gold reduced the AUDPC value by 75% and 40% on susceptible and moderately resistant varieties, respectively. Grain yield loss was estimated to be 35 to 40 % and 74 to 85 % in moderately resistant and susceptible variety, respectively. There was not significance difference (p< 0.05) observed between spray intervals in controlling ALS and increasing grain yield. This study indicated that, use of fungicides most effective in controlling ALS causing agent, reducing yield loss and obtaining net return. Therefore, integrating selected fungicides with other management options is very important to obtain optimum economic return from common bean production.